Structural insights into the modulatory role of the accessory protein WYL1 in the Type VI-D CRISPR-Cas system. Issue 10 (12th April 2019) - Zhang, Heng; Dong, Cheng; Li, Li; Wasney, Gregory A; Min, Jinrong
Abstract: The Type VI-D CRISPR-Cas system employs an RNA-guided RNase Cas13d with minimal targeting constraints to combat viral infections. This CRISPR system contains RspWYL1 as a unique accessory protein that plays a key role in boosting its effector function on target RNAs, but the mechanism behind this RspWYL1-mediated stimulation remains completely unexplored. Through structural and biophysical approaches, we reveal that the full-length RspWYL1 possesses a novel three-domain architecture and preferentially binds ssRNA with high affinity. Specifically, the N-terminus of RspWYL1 harbors a ribbon-helix-helix motif reminiscent of transcriptional regulators; the central WYL domain of RspWYL1 displays a Sm-like β-barrel fold; and the C-terminal domain of RspWYL1 primarily contributes to the dimerization of RspWYL1 and may regulate the RspWYL1 function via a large conformational change. Collectively, this study provides a first glimpse into the complex mechanism behind the RspWYL1-dictated boosting of target ssRNA cleavage in the Type VI-D CRISPR-Cas system.